Origins of Human Language Continuities and Discontinuities with Nonhuman Primates - Boë, Louis-Jean; Fagot, Joël; Perrier, Pascal; Schwartz, Jean-Luc (Speech Production and Perception, 2017)
This book proposes a detailed picture of the continuities and ruptures between communication in primates and language in humans. It explores a diversity of perspectives on the origins of language, including a fine description of vocal communication in animals, mainly in monkeys and apes, but also in birds, the study of vocal tract anatomy and cortical control of the vocal productions in monkeys and apes, the description of combinatory structures and their social and communicative value, and the exploration of the cognitive environment in which language may have emerged from nonhuman primate vocal or gestural communication.